Exploring the Impact of Digital Finance on Regional Innovation Efficiency: Evidence from China - Li, Yifan (International Journal of Social Sciences and Public Administration, 2024)
Digital finance, as an innovative financial approach, has drawn increasing attention due to its potential to shape regional innovation. This study delves into how digital finance interacts with regional innovation efficiency, beginning with an exploration of the underlying mechanisms. Using data from 31 provinces in China spanning the years 2011 to 2023, and applying a dynamic spatial Durbin model, we examine the spatial spillover effects of digital finance. The analysis uncovers a strong spatial interdependence and temporal persistence in regional innovation efficiency throughout the observed period. The results suggest that digital finance significantly enhances innovation efficiency at the regional level, with pronounced spatial spillover effects. The breakdown of spatial effects indicates that the indirect spillover impact of digital finance surpasses its direct influence. Furthermore, each dimension of digital finance shows spatial spillover, and the disparity between eastern and central-western regions is primarily evident in the spatial spillover patterns of digital finance.